Morphological Changes of Placenta in Preeclampsia - Kishwara, Segupta; Ara, Shamim; Rayhan, Khandaker Abu; Begum, Mahamuda (Bangladesh Journal of Anatomy, 2009)
Context: Preeclampsia is regarded as a risk factor in pregnancy and it leads to placental insufficiency. This, in turn causes both maternal and fetal morbidity and mortality. The present study intends to compare the morphological changes of placenta in preeclampsia with that of normal placenta. Study design: A descriptive type of study. Place and period of study: Department of Anatomy, Dhaka Medical College, Dhaka, from August 2005 to June 2006. Materials: 60 human placentae, 30 were from normal pregnant women as control and 30 from pregnancies complicated by preeclampsia were taken for this study. Method: Samples were grouped as Group A and Group B on the basis of presence or absence of preeclampsia. All samples were studied morphologically. Result: Different shapes of placenta were found with some having accessory lobes in both groups. There was significant reduction (p< 0.001) in diameter and volume of placenta in Group B. The thickness of placenta was reduced in Group B but the difference did not reach a significant level. The number of cotyledon was significantly reduced in Group B (p<0.05). Conclusion: In this study, it was found that the preeclamptic placentae underwent definite morphological changes. These changes seemed to be the result of insufficiency of placenta in preeclampsia. However, further histological and morphometric placental study in a larger sample has to be conducted to come up with a conclusive decision. Key Words: Placenta, Preeclampsia, Morphology. doi: 10.3329/bja.v7i1.3026 Bangladesh Journal of Anatomy January 2009, Vol. 7 No. 1 pp. 49-54